The Influence of Environmental Performance, Profitability, and Leverage on Firm Value in Indonesia - Nada Noor Ariska; Soelistijono Boedi; Saifhul Anuar Syahdan; Gemi Ruwanti (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2026)
This study aims to analyse and examine the influence of environmental performance, profitability, and leverage on firm value in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2024 period. Environmental performance is measured using companies' ratings in the Corporate Performance Rating Program in Environmental Management (PROPER); profitability is measured using Return on Assets (ROA); leverage is measured using the Debt-to-Equity Ratio (DER); and firm value is measured using Price-to-Book Value (PBV). This study employs a quantitative approach using secondary data from company annual reports. The sample was selected using purposive sampling. Based on predetermined criteria, 20 companies were included in the research sample. Multiple linear regression analysis was used to determine the effects of the independent variables on the dependent variable. The results indicate that environmental performance does not affect firm value, profitability has a positive effect on firm value, and leverage does not affect firm value. These findings suggest that investors tend to place greater emphasis on the company’s ability to generate profits than on environmental performance and debt levels when assessing firm value.